Skill-biased employment and the stringency of environmental regulations in European countries - José Alberto Fuinhas; Asif Javed; Dario Sciulli; Edilio Valentini (Fondazione Eni Enrico Mattei (FEEM), 2025)
Governments across the globe are implementing stricter environmental policies to combat climate change and promote sustainability. This study contributes to the growing literature exploring the influence of environmental policy on skill-biased employment across various occupations. Specifically, we examine the causal effect of the revised version of Environmental Policy Stringency Index (EPS) and its components on skill-biased employment, focusing on occupations such as managers, professionals, technicians, and manual workers across 21 European economies from 2008 to 2020. Using the Method of Moments Quantile Regression (MMQR), the findings reveal that stringent environmental policies affect employment shares across different occupational categories. Skilled workers tend to benefit more from such policies, with a notable increase in the employment of professionals across all policy measures and a more differentiated impact among technicians and managers. In contrast, manual workers are generally adversely affected by environmental policies. These asymmetric effects on occupations exacerbate labour market inequalities, including disparities in employment levels and potential earnings. This research highlights the importance of designing tailored policies to mitigate adverse labour market outcomes while facilitating a transition to sustainable economic practices.
Keywords: Q58; J24; 330; Environmental policy stringency; Skilled workers; Employment; Method of Moments Quantile Regression